ANALISIS FRAMING PEMBERITAAN GANJAR PRANOWO TERKAIT PENOLAKAN TERHADAP KEIKUTSERTAAN TIMNAS ISRAEL DALAM PIALA DUNIA U20 INDONESIA ANALISIS FRAMING PEMBERITAAN GANJAR PRANOWO TERKAIT PENOLAKAN TERHADAP KEIKUTSDI DETIK.COM (Periode 23 Maret – 1 April 2023) - Linuwih, Risang Adi; Sarjono, Herning Suryo; Kusumo Aji, Haryo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Ganjar Pranowo is one of the presidential candidates contesting in the 2024 election. Based on a survey conducted by LSI in 2023, Ganjar Pranowo has the highest electability with a percentage of 37 percent. However, in March 2023, Ganjar Pranowo issued a controversial statement rejecting Israel's participation in the U20 World Cup in Indonesia. A few days after his statement, FIFA revoked Indonesia's hosting rights. After the incident, Ganjar Pranowo also received attention from various online news portal media, including DETIK.COM which is the most popular and largest online news portal in Indonesia. The framing DETIK.COM of the incident becomes interesting in the midst of election season and the strong influence of the mass media. Therefore, this study aims to find out the framing of Ganjar Pranowo's news that rejected Israel's participation in the U20 World Cup. This research uses qualitative methods and is analyzed using Zhongdang Pan & Kosicki's framing analysis theory with four tools (Syntax, Script, Thematic, Rhetorical). The conclusion of this study also shows how DETIK.COM framed Ganjar Pranowo as a cadre loyal to his Party's ideology which is upright to Karno's mandate in fighting for Palestinian independence. In addition, Ganjar is considered guilty of failing the U20 World Cup, as well as being a figure who is threatened with a decline in his electability as a Presidential Candidate, following Indonesia's failure to host the U20 World Cup Keywords: Framing Analysis, DETIK.COM, Ganjar Pranowo, U20 World Cup Issues.